Sustainability Reporting Practices in the Healthcare Products Sector – the Case of Europe and North America - Berniak-Woźny, Justyna; Kwasek, Artur (Comparative Economic Research. Central and Eastern Europe, 2020)
The Paper’s goals: For the last two decades, sustainability reporting has increasingly been gaining the attention of managers, and consequently, academicians, too. This is due to the growing interest of a wide range of stakeholders, such as governments, investors, and customers, in non-financial information disclosed by business and public organisations. However, designing and implementing a sustainability report that fits the needs of these different stakeholder groups is a challenge. The differences between the various sectors make this challenge even greater. The focus of this paper will be on the healthcare products sector. The aim of this paper is to investigate the scope and quality of sustainability reporting practices of companies operating in the European and North American healthcare products sector. Research methods: The study is based on the current literature on sustainability reporting and non-financial (NFI) reporting. The empirical part of the paper will be based on a qualitative descriptive research design. Content analysis will be conducted on sustainability reports issued in 2018 and 2019, by 11 European and 8 North American organisations in the healthcare products sector. The nature of the study will be descriptive and based solely on information from secondary data sources. Expected results of the research: This paper will contribute to the international health management literature and to the existing research of sustainability reporting. Based on the findings, the health sector’s sustainability reporting practices will be carefully identified. The authors will also compare the practices of North American and European organisations’, and subsequently, they will define the trends and best practices in this field.